Letter (copy) : Basque Children - Tewson, Vincent
1940-09-12 038-0039-001 Secretary's. HVT/FC/721. Mr. E.J. Butler, 5, Alton Terrace, North Hill, PLYMOUTH. 12th September, 1940. Dear Mr. Butler, BASQUE CHILDREN I am in receipt of your letter of the 9th instant in regard to the above matter. You will appreciate, of course, that the twelve children who are cared for in Plymouth are only a small section of the three hundred children who are at present in this country. The Trades Union Congress is associated with the National Committee for the Care of Basque Children and any financial assistance it has been able to afford has been given direct to the National Committee. Under the circumstances you will see that any national Trade Union levy for the benefit of the children in Plymouth is not a practicable proposal. No doubt you have been in touch with the National Committee for the Care of Basque Children. I am sure that you will not assume that I do not appreciate your difficulties as I am personally connected with the Barnet Home which is self-supporting and is catering for forty children. Yours sincerely, Assistant Secretary. 292/946/38/39(I)